2022
DOI: 10.1038/s41531-022-00300-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics implicate gut microbiota in altered lipid and energy metabolism in Parkinson’s disease

Abstract: We aimed to investigate the link between serum metabolites, gut bacterial community composition, and clinical variables in Parkinson’s disease (PD) and healthy control subjects (HC). A total of 124 subjects were part of the study (63 PD patients and 61 HC subjects). 139 metabolite features were found to be predictive between the PD and Control groups. No associations were found between metabolite features and within-PD clinical variables. The results suggest alterations in serum metabolite profiles in PD, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…S14). Previous analyses based on multiomics approaches of the same cohort (but using samples taken two years later than the ones used in this study) indicated that metabolites involved in the squalene and cholesterol pathways could be used as predictive molecules [ 8 ], and the BGCs detected in this study could be potentially involved in the synthesis of these metabolites.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…S14). Previous analyses based on multiomics approaches of the same cohort (but using samples taken two years later than the ones used in this study) indicated that metabolites involved in the squalene and cholesterol pathways could be used as predictive molecules [ 8 ], and the BGCs detected in this study could be potentially involved in the synthesis of these metabolites.…”
Section: Discussionmentioning
confidence: 90%
“…Following the Braak hypothesis, we have also investigated the microbiome and PD connections in samples from nasal and oral locations [ 6 ]. These original microbiome analyses have been followed by studies on SCFA and immune responses [ 7 ], and recently on the links between metabolomics, metabolic enzymes, and epigenetic regulation of the host [ [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent multi-omics study revealed a strong link between the composition of the gut bacterial community, serum metabolic profile, and disease severity in patients with PD [ 40 ]. Therefore, we speculated that L. plantarum CCFM405 might affect serum metabolite composition in mice by modifying the intestinal microbiota composition and microbial metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic performance of NN was at least 10% higher than previously reported by Gonzalez-Riano et al when a SVM model was used. 13 In addition, the diagnostic performance obtained using NN is the highest reported to date for any PD diagnosis regardless of the sample matrix including blood plasma, 25,26 blood serum, 27 and skin sebum. 10,11,16,28,29 Diagnostic Performance Is Uncompromised by Including the Whole Metabolomics Dataset.…”
Section: T H I S C O N T Ementioning
confidence: 87%